(untitled) (Revista Argentina de Musicología, 2016)
Pointing to the general aim of contributing to a social history of the industry of Argentine musical folklore, this paper focuses on the way those perspectives are brought together within it, which are here labeled “learned” and feeds off the stylistic and aesthetic refinement characteristic of the “cultured” realm. After some consideration of the general relationships between folklore, musical industry and identity; and a characterization of learned identities in general terms, two modalities of learned identities are distinguished, in historical, ideological and aesthetic terms, each of one, in turn, directly influential in some given stage on the development of the industry of argentine musical folklore, although both of them have persistently reproduced themselves up to this day. One of them, already active in the foundational moments of the industry, assumes the romantic intellectual perspective, understanding folklore as the naïve expression of some popular spirit, to be elevated by the work of the “great artists”. The other one, which shows up clearly already in the 1960, proposes some explicit historization of beauty, consistent with the historicist perspective they assume for the conception of people itself.